Political Ethics In The Selection Of Local Head Candidates Fiqhi Siyasah Perspective - Darna (Jurnal Al Tasyri'iyyah, 2021)
Political ethics serve as the foundation for anybody who aspires to be a leader. However, political life in the modern era is far from ideal. Numerous politicians employ a variety of strategies to further their goals without regard for ethical standards and principles. Politicians seeking power employ a variety of strategies, including making reckless political promises. The purpose of this study is to ascertain the public's opinion of the candidate pairs' political ethics, the elements that influence their application during elections, and the relationship between political ethics in the context of fiqhi siyasah and political ethics in Banggae District. This study employs a Normative Syar'i and Sociological Phenomenology approach. The data are derived from primary and secondary sources. The findings indicated that the public had a favorable opinion of the political ethics of the candidate pairs in the 2020 regional elections. Judging by the candidate pair's attitude in the community and their commitment to regional development and growth. Political ethics were affected by elements such as legal understanding, religious devotion, and level of education for regional head candidates in the 2020 regional head elections. Political ethics in the 2020 Pilkada in Banggae District are consistent with Fiqhi Siyasah in terms of conducting a campaign that is fair and adheres to regulations, as well as the attitudes and behavior of candidate pairs in the community. Keywords: Political Ethics; Regional Legislative Elections; Fiqhi Siyasah